2003
DOI: 10.1002/cvde.200306246
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Independent Palladium Atomic Layer Deposition

Abstract: A novel method is presented for the atomic layer deposition (ALD) of palladium on a tetrasulfide self-assembled monolayer functionalized SiO 2 surface. Additionally, a novel reducing agent (glyoxylic acid) was used to remove the organic ligands from the chemisorbed palladium(II) hexafluoroacetylacetonate metallorganic. Glyoxylic acid is an effective reducing agent above 200 C, which is not optimal for palladium but it is effective enough to show proof-of-concept and deposit a Pd ªseedº layer. Palladium was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…10 Senkevich et al demonstrated Pd ALD at 80 °C on Ir metal surfaces, where atomic hydrogen, formed from the dissociation of H 2 on the Ir surface, served as the reducing reagent. 11 To increase the substrate generality, Ten Eyck et al used a remote hydrogen plasma for Pd ALD on Ir, W, and Si surfaces. 12 However, plasmas are not well suited to catalyst synthesis because they require line-of-site between the plasma and the substrate surface which is impractical for nanoporous catalyst templates.…”
Section: Palladium Aldmentioning
confidence: 99%
“…10 Senkevich et al demonstrated Pd ALD at 80 °C on Ir metal surfaces, where atomic hydrogen, formed from the dissociation of H 2 on the Ir surface, served as the reducing reagent. 11 To increase the substrate generality, Ten Eyck et al used a remote hydrogen plasma for Pd ALD on Ir, W, and Si surfaces. 12 However, plasmas are not well suited to catalyst synthesis because they require line-of-site between the plasma and the substrate surface which is impractical for nanoporous catalyst templates.…”
Section: Palladium Aldmentioning
confidence: 99%
“…[6] To date, Pd ALD has not achieved success on oxideterminated surfaces primarily due to the lack of chemisorption of palladium(II) hexafluoroacetylacetonate, Pd II -(hfac) 2 . [12,13] Additionally, there has been a lack of suitable reducing agents. Senkevich et al [12] successfully demonstrated the use of thermally cleaved glyoxylic acid as a reducing agent for Pd ALD, but this technique required substrate temperatures in excess of 200 C, which only yielded a monolayer seed' layer whereupon hydrogen could be used at 80 C. Hydrogen can only be utilized with thermal ALD when a catalytic surface is present for the dissociation of molecular hydrogen to atomic hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…RHEED is widely used for in situ analysis of (crystalline) growth in pulsed laser deposition (PLD) and molecular-beam epitaxy (MBE) systems. Several ALD layers have been studied using ex situ RHEED, [6][7][8] although the photographs of the diffraction patterns are only presented to show (non)crystallinity of the deposited layers. A beam of high energy electrons (5-35 keV) is reflected off the sample surface at grazing incident angles, usually 1°-3°w ith respect to the wafer surface.…”
Section: Introductionmentioning
confidence: 99%